Wednesday

July 23, 2014

July 23, 2014

Posted by **Veronica** on Wednesday, July 23, 2008 at 8:10pm.

Using the chain rule...I figured out my previous post.

- Calculus -
**drwls**, Thursday, July 24, 2008 at 12:09amh(x) = 7x *(5-2x)^-1/2

dh/dx = 7 (5-2x)^-1/2

+ (7x)d/dx(5-2x)^-1/2

Use the chain rule on the second term

d/dx(5-2x)^-1/2 = (-1/2)(-2)(5-2x)^-3/2

= (5-2x)^-3/2

**Related Questions**

Math, Calculus - Find the derivative of the function. y= xcosx - sinx What's the...

calc - find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find ...

Calculus - Can anyone explain how to use the chain rule and power rule together ...

MoRe HeLp PlEaSe!! (calc) - Also can I get some help with this LONG, TIRESOME ...

calculus - Please help. Applying the chain rule, how do I find the derivative of...

Calculus - How do I use the chain rule to find the derivative of square root(1-x...

calculus - find the derivative using quotient rule F(x) = (x - 7 x sqrt(x)) / ...

CAlculus - using chain rule find the derivative of y=xsin1/x

Calculus (Help) - Also I would like to know how to set this problem up in ...

calculus - Find the derivative of the function below in two ways. F(x) = (x - 7 ...